Fecal Microbiota Changes in Angus Beef Cows Persistently Infected by Bovine Viral Diarrhea Virus - Ruiyang Xia; Yalu Chen; Pengfei Yi; Yawei Sun; Lijing Chen; Xuelian Ma; Qi Zhong; Na Li; Gang Yao (Veterinary Sciences)
Bovine viral diarrhea virus (BVDV) remains a major cause of calf diarrhea with substantial economic impacts on global cattle production. While emerging evidence suggests that the host microbiota may modulate viral infection processes, the specific gut microbial alterations induced by BVDV infection require elucidation. This study investigated gut microbiota composition and functional changes in BVDV-infected cows through 16S rRNA sequencing. Following the epidemiological screening of a large Angus cattle herd using RT-PCR, we identified four persistently infected (PI) animals and four BVDV-negative controls. Fecal analysis revealed Firmicutes and Bacteroidetes as dominant phyla in both groups. A significant increase in the Ruminococcus genus was observed in PI cows (p < 0.05), with LEfSe analysis identifying Paludibacter as a BVDV-associated biomarker. The PI group exhibited reduced alpha diversity (Faith’s PD index, p < 0.05) and elevated histidine metabolism pathway abundance compared to controls (p < 0.05). These findings demonstrate that persistent BVDV infection induces structural and functional modifications in the bovine gut microbiota, particularly through the enrichment of specific bacterial taxa and altered metabolic potential. The results provide new insights into virus–microbiota interactions, establishing a foundation for understanding how BVDV infection may influence host physiology through microbial community changes.